1989
DOI: 10.3758/bf03204993
|View full text |Cite
|
Sign up to set email alerts
|

Length distortion of temporally extended visual displays: Similarity to haptic spatial perception

Abstract: Three experiments were designed to investigate length distortion-the tendency to inflate estimates of the inferred distance between two points, as the length of a circuitous pathway between them increases. This phenomenon, previously demonstrated with haptic and locomotor exploration (Lederman, Klatzky, Collins, & Wardell, 1987), was extended to vision through the presentation of pathways as a temporal sequence of illuminated points. The magnitude of the visual effect was less than that previously found in hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Furthermore, this cannot explain the lack of an effect of line orientation with the smallest patterns, a finding that is consistent with earlier reports in the literature (e.g., Hatwell, 1960). Other researchers have previously reported overestimations of tactually experienced extent (Balakrishnan, Klatzky, Loomis, & Lederman, 1989). Balakrishnan et al reported that overestimation was far more common with slower rates ofexploration.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, this cannot explain the lack of an effect of line orientation with the smallest patterns, a finding that is consistent with earlier reports in the literature (e.g., Hatwell, 1960). Other researchers have previously reported overestimations of tactually experienced extent (Balakrishnan, Klatzky, Loomis, & Lederman, 1989). Balakrishnan et al reported that overestimation was far more common with slower rates ofexploration.…”
Section: Discussionsupporting
confidence: 74%
“…If there is more uncertainty or distortion associated with the kinesthetic monitoring of hands and fingers than with that of the eyes (relative to the size of the patterns being scanned), as appears plausible (Klatzky and Lederman 1987;Balakrishnan et al 1989), then one would expect touch to be at some disadvantage relative to vision in the integration of successive patterns of receptor activation.…”
Section: Introductionmentioning
confidence: 96%
“…Temporal and spatial acuity also is poorer in touch than vision (Loomis & Lederman, 1986). Uncertainty and distortion associated with the kinesthetic monitoring of the hand and fingers seems to be greater compared with the eyes (Balakrishnan, Klatzky, Loomis, & Lederman, 1989;Klatzky & Lederman, 1987). Finally, some of the stimulus materials derived from visual studies may be less familiar in terms of touch (Heller, 1989;Kennedy, 2000;Kennedy & Fox, 1977;Lederman et al, 1990).…”
mentioning
confidence: 97%